2013
DOI: 10.1590/s0102-311x2013000200003
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity and excess weight/obesity among Brazilian women and children: a life-course approach

Abstract: Household food insecurity (HFI) may increase obesity risk, but results are not consistent across the life course or between developed/underdeveloped settings. The objective of this paper is to review findings from previous analyses in Brazil among adult women, female adolescents, and children up to five. Data were derived from the 2006 Brazilian Demographic and Health Survey. Associations between HFI (measured with the Brazilian Food Insecurity Scale) and excess weight/obesity were investigated through Poisson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 23 publications
2
29
1
18
Order By: Relevance
“…Identificou-se que em 39,8% dos domicílios com mulheres, 41,3% dos domicílios com adolescentes e 48,6% dos domicílios com crianças identificou-se situação de insegurança alimentar 46 .…”
Section: Resultsunclassified
“…Identificou-se que em 39,8% dos domicílios com mulheres, 41,3% dos domicílios com adolescentes e 48,6% dos domicílios com crianças identificou-se situação de insegurança alimentar 46 .…”
Section: Resultsunclassified
“…Some studies have shown a relationship between food insecurity and anthropometric and nutritional indicators for overweight and obesity [13][14][15] , while other studies have presented data showing significant associations between food insecurity and malnutrition and nutrient deficiency 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…La protección de la LME<6m se espera que sea mayor en niños más vulnerables, 1 que viven en hogares con IA moderada y severa, hogares donde hay más pobreza, insalubridad, mayor relación niños/adultos, menor acceso a servicios de salud, mayor incidencia de infecciones y mayor rezago social comparados con hogares en SA. [7][8][9][10][11][12] En el presente estudio no se documentó esta misma relación protectora de la LME<6m en la longitud de los pequeños; i.e., la diferencia de la longitud para la edad (Z L/E) no fue estadísticamente significativa entre niños de hogares con o sin SA. Estos hallazgos tienen un significado particularmente importante en términos de salud pública infantil porque resaltan el papel protector de la LME<6m contra el bajo peso para la longitud; que cuando es bajo se define como desnutrición aguda.…”
Section: Discussionunclassified
“…[7][8][9][10][11][12] Pocos estudios han explorado el papel de la lactancia en familias en inseguridad alimentaria, y los hallazgos son mixtos. En Brasil, la IA se asocia a una mayor duración de lactancia 13 mientras que en inmigrantes en Estados Unidos, la IA se asoció a una duración más corta.…”
unclassified